On the Specification and Simulation of a Regional Econometric Model: A Model of Mississippi - Adams, F. Gerard; Brooking, Carl G.; Glickman, Norman J. (The Review of Economics and Statistics, 1975)
F. Gerard Adams, Carl G. Brooking, Norman J. Glickman, On the Specification and Simulation of a Regional Econometric Model: A Model of Mississippi, The Review of Economics and Statistics, Vol. 57, No. 3 (Aug., 1975), pp. 286-298